2014
DOI: 10.1159/000351683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Skin Metabolism on Dermal Delivery of Testosterone: Qualitative Assessment using a New Short-Term Skin Model

Abstract: The skin is a metabolically active organ expressing biotransformation enzymes able to metabolize both endogenous molecules and xenobiotics. We investigated the impact of metabolism on the delivery of testosterone through the skin with an ex vivo pig ear skin system as an alternative model for human skin. Penetration, absorption and metabolic capabilities were investigated up to 72 h after application of [14C]-testosterone doses of 50-800 nmol on either fresh or frozen skin, with the latter model bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…This is in contrast to the findings of Hewitt et al [5], who reported that the passage of the larger-molecular-weight and lipophilic chemicals fluoxypyr esters from the SC into the epidermis required cleavage of the ester to a more hydrophilic metabolite. Likewise, benzo(a)pyrene also requires metabolism to more hydrophilic metabolites before it can penetrate the epidermis and dermis [6,7]. With this in mind, the penetration and metabolism of some chemicals known to be metabolized by dermal metabolizing enzymes should be determined using fresh human skin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast to the findings of Hewitt et al [5], who reported that the passage of the larger-molecular-weight and lipophilic chemicals fluoxypyr esters from the SC into the epidermis required cleavage of the ester to a more hydrophilic metabolite. Likewise, benzo(a)pyrene also requires metabolism to more hydrophilic metabolites before it can penetrate the epidermis and dermis [6,7]. With this in mind, the penetration and metabolism of some chemicals known to be metabolized by dermal metabolizing enzymes should be determined using fresh human skin.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for lower penetration of certain chemicals (e.g., benz(a)pyrene) in frozen skin is mainly due to inactivation of metabolizing enzymes [6,7], which is why our studies were specifically designed to compare chemicals that were not metabolized by dermal enzymes. For all 3 chemicals, the amounts recovered in the epidermis and dermis were very low and represented less than 2% of the applied dose; therefore, the statistical differences determined in these layers for BA were considered not to be biologically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porcine skin is readily available from slaughterhouses, and its histological and biochemical properties have been repeatedly shown to be similar to human skin [9,10]. Therefore, in addition to human skin, we have also evaluated the effect of skin damage on a pig skin model, previously developed using skin explants from domestic pig ears [11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…Differences for two chemicals were attributed to a lack of appropriate cofactor in S9 incubations and protein binding influencing chemical uptake in skin explants. Metabolism is a key step that can modulate skin absorption of topically applied chemicals and thus greatly affect skin bioavailability, as reported by Jacques et al for benzo[a]pyrene and testosterone (Jacques, Perdu, Duplan, et al, 2010;Jacques et al, 2014). approaches, reference methods to identify toxicants were based on animal tests that inherently integrate bioavailability; however, these are now banned according to the 7th Amendment to the Cosmetics Directive (EU, 2003).…”
mentioning
confidence: 99%